Exploring the black box of French community supervision - Herzog-Evans, Martine (European journal of probation, 2023)
This article explores how probation officers (POs) in France employ evidence-based practice in the real world. Using 78 audio tapes of 11 POs and 33 offenders in 2 probations services, we assessed PO skills with an adapted version of the Jersey Checklist. Our results suggest that French probation officers generally possess good communication skills, and use – to a certain extent – core correctional practices. They do, however, underperform with regard to cognitive behavioural techniques.